Síntese e Análise Estrutural de Complexos de Urânio (VI) e Tório (IV) com Ligantes Relacionados a N,N -bis-piridoxilidenoimina - Vargas, Jaqueline Pinto (2010)
This work presents a study related to the synthesis and structural analysis of complexes of uranium (IV) and thorium (IV) with ligands related to N,N -bispiridoxilideneimine. Pyridoxine chlorhydrate and aliphatic and aromatic chain primary amines were used as starting material for synthesis of ligands beyond uranyl and thorium nitrates for synthesis of complexes. The compounds synthesized were: [UO2(pyr2pen)(CH3OH)] (1), [Th(pyr2pen)2] (2), UO2(pyr2dien)]·2H2O (3), [UO2(H2pyr2phen)Cl](NO3)·2H2O (4) and [UO2(Hpyr2phen)Cl]·H2O (5). A structural study of these compounds in solid state was made as a tool the X-ray diffraction in single crystal. All compounds were also characterized by elemental analysis and infrared spectroscopy.